Chemical Constituents and Biological Activities of Phragmanthera incana (Schum.) Balle Harvested from Cola acuminata Schott and Endl. Tree - Atewolara-Odule, Odunayo C.; Aiyelaagbe, Olapeju O.; Goosen, Eleonora D.; Olubomehin, Oseyemi O.; Ajibade, Sunday. O.; Ogunmoye, Abdulrazaq O.; Akoro, Seide M. (Journal of Nepal Chemical Society, 2026)
Plants serve as the major source of medicine for many diseases in developing countries. Phragmanthera incana (Loranthaceae) is used in traditional medicine to treat diabetes, inflammation, and cancer. However, there is a dearth of information on its chemical composition. The study aims to isolate and characterise the chemical constituents of Phragmanthera incana and assess its pharmacological activities. The air-dried leaves and stem of the plant were pulverised and macerated with ethyl acetate and methanol, which yielded respective crude extracts. The extracts were tested for cytotoxicity and antioxidant activity using brine shrimp lethality test and 1,1-diphenyl-2-picrylhydrazyl, respectively. The anti-diabetic activity was assessed using alloxan-induced rats with glibenclamide as reference drug. Data were subjected to descriptive statistics. The ethyl acetate extract of the plant was subjected to chromatographic techniques. The isolated compounds’ structures were determined using Mass Spectrometry, Fourier-transform Infrared Spectroscopy, and NMR Spectroscopy. The crude extracts’ percentage yield ranged from 0.43 to 1.63 % while the crude extracts’ weight ranged from 6.0 to 22.0 g. The extracts exhibited cytotoxicity against brine shrimps with LC50 0.49-188.8 µg/mL except for the ethyl acetate extract of leaves and stem of P. incana that were non-toxic with LC50 ˃ 1000 µg/mL. All extracts and isolated compounds exhibited antioxidant potency with radical scavenging activity ranging from 57.99-92.62%, and 73.15-87.68% respectively. There was reduction in the percentage of blood glucose (71.8%) of alloxan-induced diabetic rats treated by the extracts compared to that of glibenclamide’s reduction (53.0%). Friedelin, canophyllol, and eudesmic acid were isolated from P. incana leaves. Phragmanthera incana contained some bioactive constituents that are potential candidates for the treatment of diabetes and oxidative stress-induced pathology.